RISALAH SAKRAT AL-MAUT KARYA ABDURRAUF SINGKEL (Penelitian Filologis Atas Naskah Nagara) - Fathullah Munadi, Abu Qasim, Muhammad Yusuf, (Al-Banjari : Jurnal Ilmiah Ilmu-Ilmu Keislaman, 2015)
The Text of Sakrat al-Maut written by Abdurrauf Assingkili that was collected along with the text of Syar?b al-?syiq?n written by Syekh Hamzah Fansuri and the text of Hujjatus Shidd?q written by Syekh Nuruddin Arranir as well as other writings in the manuscript of Nagara strengthens the influence of the Islamic scholars on Islamic studies in Banjar. Philologically, this manuscript was regarded as a copy made in the 19th century, and it was not the initial manuscript written by Sheikh Abdurrauf in the 17th century. The circulation of Sakrat al-Maut manuscripts is not widespread. It is evident with the minimal number of manuscripts that were found / recorded in the catalog. In Banjar, the teachings contained in the manuscript text of Sakrat al-Maut is not fully adopted by next Banjar scholars.